Photooxidative Coupling of Thiols Promoted by Bromo(trichloro)methane in a Basic Aqueous Medium - Shan, Shiquan; Pang, Songhao; Qu, Yunwei; Lu, Yongna; Cheng, Xiamin; Li, Lin (Synlett, 2023)
A transition-metal- and organic-solvent-free oxidative coupling of thiols catalyzed by BrCCl3 and NaOH in an aqueous medium with oxygen as a green oxidant was established The facile and green method has a broad substrate scope in converting thiols into the corresponding disulfides with medium to excellent yields (up to 91%). This method could potentially be used to construct bioactive molecules containing disulfide bonds and to label bioactive molecules with disulfide bonds.
Keywords: photocatalysis; coupling; free radicals; photooxidation; thiols; disulfides